The position receipt As a Proof of Land Sale and Purchase in the Conception of Legal Certainty - Ariza, Billy (Jurnal Konstatering, 2022)
This study aims to examine and analyze the position receipt As evidence of buying and selling land in the conception of legal certainty. To analyze legal consequencesreceiptsale and purchase of land in the concept of legal certainty. The research approach method used in this thesis is an empirical juridical legal research method and the nature of this research is analytical descriptive.Data collection was carried out through a literature studyin order to obtain secondary data, whether in the form of primary legal materials, secondary legal materials, or tertiary legal materials.To support the research that has been done, field research was also carried outin order to obtain primary data that supports secondary data. The technical analysis used in this study is a qualitative analysis technique. The research results show thatthe fulfillment of the elements of sale and purchase (agreement) as contained in Article 1320 of the Civil Code in conjunction with Article 1457 of the Civil Code.Even though buying and selling underhand is legal based on the principle of freedom of contract and the existence of an agreement between the parties, it cannot be said to be valid in managing the registration process for the transfer of names because there are several administrative requirements that have not been met, namely formal requirements and to obtain the transfer of land rights and transfer of names. must have a deed drawn up by PPAT because the transfer of land rights through buying and selling land must be proven by a deed drawn up by PPAT. Because of lawinside receiptsale and purchase of land rights carried out privately, if a dispute arises between the seller and the buyer, the private deed can still be refuted and only has perfect evidentiary strength if it is acknowledged by both parties, or strengthened by other evidence. Therefore, it is said that the deed under the hand is the beginning of written evidenceandIf you want to transfer the name, the parties, both the seller and the buyer, must make a sale and purchase deed drawn up by the PPAT as the basis for transferring the name at the BPN office.Keywords: Evidence; Purchase; Sale.Â